1997
DOI: 10.1111/j.1539-6924.1997.tb00859.x
|View full text |Cite
|
Sign up to set email alerts
|

An Overview of a Multimedia Benchmarking Analysis for Three Risk Assessment Models: RESRAD, MMSOILS, and MEPAS

Abstract: Multimedia modelers from the United States Environmental Protection Agency (EPA) and the United States Department of Energy (DOE) collaborated to conduct a detailed and quantitative benchmarking analysis of three multimedia models. The three models--RESRAD (DOE), MMSOILS (EPA), and MEPAS (DOE)--represent analytically-based tools that are used by the respective agencies for performing human exposure and health risk assessments. The study is performed by individuals who participate directly in the ongoing design… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

1999
1999
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(9 citation statements)
references
References 2 publications
0
8
0
1
Order By: Relevance
“…It has been shown that besides comparing model predictions with observations, the magnitude of model uncertainty can be determined by the range of results among several models [6,17,19]. Therefore, many studies have performed model comparisons to investigate the differences among models; in particular, a series of papers compared MEPAS, MMSOILS, and RESRAD [20][21][22][23]. Table 1 The representative classifications of uncertainty in the literature Finkel [5] USEPA [6] Cullen and Frey [8] Parameter Through simulating several cases, these studies have observed obvious differences, which are as large as two or even three orders of magnitude, of risk estimates in various models due to different environmental processes considered, mathematical formulations used, and scenario assumptions made.…”
Section: Uncertainty In Risk Assessment Modelingmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown that besides comparing model predictions with observations, the magnitude of model uncertainty can be determined by the range of results among several models [6,17,19]. Therefore, many studies have performed model comparisons to investigate the differences among models; in particular, a series of papers compared MEPAS, MMSOILS, and RESRAD [20][21][22][23]. Table 1 The representative classifications of uncertainty in the literature Finkel [5] USEPA [6] Cullen and Frey [8] Parameter Through simulating several cases, these studies have observed obvious differences, which are as large as two or even three orders of magnitude, of risk estimates in various models due to different environmental processes considered, mathematical formulations used, and scenario assumptions made.…”
Section: Uncertainty In Risk Assessment Modelingmentioning
confidence: 99%
“…These models are also designed for screening-level tools and site-specific risk assessments for regulatory development and standard setting [20]; however, the different environmental processes considered, mathematical formulations used, and scenario assumptions made in these models will cause different results, and thus model uncertainty. The scenario considered in this case study is that the residents use groundwater for irrigation and domestic purposes.…”
Section: The Case Of Contaminated-groundwater Risk Assessmentmentioning
confidence: 99%
“…More details of MEPAS and MMSOILS and their application can be found elsewhere [7,[9][10][11][12][13].…”
Section: Model Description and Risk Analysismentioning
confidence: 99%
“…source pollution loads (Argent, 2005), the impact of agricultural management practices (e.g., Donatelli et al, 2006), simulation of water soil dynamics (Leavesley et al, 1996), and the qualitative aspects of crop production (Cappelli et al, 2014). Given that most environmental problems benefit from a multidisciplinary analysis (Whelan et al, 2014), the availability of framework-independent software components strongly fosters the development of modelling solutions that integrate single-discipline approaches (Laniak et al, 1997;Donatelli et al, 2014).…”
Section: Introductionmentioning
confidence: 99%